Translation and Quality Management: some implications for the theory, practice and teaching of translation - Petersen, Margrethe (HERMES - Journal of Language and Communication in Business, 2017)
The aim of this article is to consider the issue of quality in translation. Specifically, the question under consideration is whether quality assurance in relation to translation is feasible and, if so, what some of the implications for translation theory, translation practice and the teaching of translation would be. To provide a backdrop against which the issue may be discussed, I present an overview of the two areas which seem most likely to hold potential answers, viz., that of translation theory and that of quality management. Section 1. gives a brief outline of some contributions to translation theory which would seem likely to be of interest in this connection and section 2. gives a linguist’s introduction to the part of the area of quality management which I consider relevant for present purposes. Section 3. is devoted to the case study of a small translation firm which has been certified under the ISO 9001 standard, and section 4. discusses the implications which quality management seems to hold for the field of translation in a broad sense. Finally, section 5. concludes the article.